Determinants of Chronic Energy Deficiency among Indonesian Women in The Preconception Period - Sundari, Fina Dewi; Afifah, Effatul; Paratmanitya, Yhona (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: This study aimed to determine the determinants of CED among Indonesian women in the preconception period. Methodology: This was a cross-sectional study involving 113 premarital women in Bantul District, Yogyakarta, Indonesia. Determinants of CED studied were socio-demographic factors, knowledge about preconception nutrition, and body mass index (BMI). Socio-demographic background was obtained through a questionnaire. Knowledge about preconception nutrition was measured using a validated questionnaire consisting of 25 questions. Height and body weight were measured using a microtoise and digital scale, respectively. Data were analyzed with Chi-Square test and multiple logistic regression, with statistical significance at α=0.05. Results: The overall prevalence of CED was 26.5%. Majority of the premarital women were ≤25 years old (65.5%), work (65.9%), and only 24.8% had higher education. The proportion of underweight and overweight was 18.6% and 28.3%, respectively. The result from multiple logistic regression showed that factors associated with CED were age and BMI (Odds Ratio [OR] 8.5, 95% confidence interval [CI] 1.54-45.99; and OR 58.2; 95% CI 11.21-302.09, respectively) Applications/Originality/Value: The difference between this research and previous research lies in the research time, research respondents, literature used, and theory used.